Effect of hemodiafiltration therapy in a low‐birthweight infant with congenital sepsis. Issue 3 (16th December 2015) - Tokumasu, Hironobu; Watabe, Shinichi; Tokumasu, Satoko
Abstract: The clinical course of congenital neonatal sepsis due to Streptococcus pneumoniae progresses rapidly and results in multiorgan failure with high mortality. The swift progression of the disease limits the timeframe for conventional treatment, which often requires waiting for antibiotics to show efficacy. Here, we describe the case of a very low‐birthweight (VLBW) female infant with congenital sepsis due to S . pneumoniae who was treated with continuous hemodiafiltration (CHDF) and polymyxin B‐immobilized fiber column–direct hemoperfusion (PMX‐DHP). The infant was born at 30 weeks' gestation and diagnosed with hypotension, disseminated intravascular coagulation, and pulmonary hypertension. CHDF and PMX‐DHP were initiated approximately 11 h after birth. Mean blood pressure, oxygenation, and blood interleukin‐6 began to improve after dialysis commencement, and the patient survived with mild sequelae. Combined CHDF and PMX‐DHP may be effective in treating VLBW infants with severe septic shock.